Kondisi Pariwisata Berkelanjutan di Bidang Sosial Budaya Berdasar Pengalaman dan Harapan Pengunjung di Pantai Tanjung Papuma, Jember - Maria Pia Adiati; Anwar Basalamah (Binus Business Review, 2014)
Jember becomes famous since the event of Jember Fashion Carnaval (JFC) which has been started since 2003. Along with the success of the JFC, Jember takes this moment to introduce the region as an attractive tourist destination in addition to JFC. Papuma beach is now a tourist icon of Jember. This beach offers a unique natural beauty as a combination of beach and forest. In the development of sustainable tourism, there are three pillars to note and they are environmental, economic and social. The purpose of this study is to determine the opinion of visitors to the state tourism Papuma Beach. This study uses descriptive qualitative approach by taking a more specific social dimension as an indicator, that is visitor satisfaction. In this study, beachgoers are asked to describe their experiences in Papuma Beach, by asking them some indicators, such as the existence of public transport, attraction, amenities, access, ancillary services, and experiences.